Clinicians' perceptions of opioid error–contributing factors in inpatient palliative care services: A qualitative study. (April 2019) - Heneka, Nicole; Bhattarai, Priyanka; Shaw, Tim; Rowett, Debra; Lapkin, Samuel; Phillips, Jane L
Background: Opioid errors are a leading cause of patient harm and adversely impact palliative care inpatients' pain and symptom management. Yet, the factors contributing to opioid errors in palliative care are poorly understood. Identifying and better understanding the individual and system factors contributing to these errors is required to inform targeted strategies. Objectives: To explore palliative care clinicians' perceptions of the factors contributing to opioid errors in Australian inpatient palliative care services. Design: A qualitative study using focus groups or semi-structured interviews. Settings: Three specialist palliative care inpatient services in New South Wales, Australia. Participants: Inpatient palliative care clinicians who are involved with, and/or have oversight of, the services' opioid delivery or quality and safety processes. Methods: Deductive thematic content analysis of the qualitative data. The Yorkshire Contributory Factors Framework was applied to identify error-contributing factors. Findings: A total of 58 clinicians participated in eight focus groups and 20 semi-structured interviews. Nine key error contributory factor domains were identified, including: active failures; task characteristics of opioid preparation; clinician inexperience; sub-optimal skill mix; gaps in support from central functions; the drug preparation environment; and sub-optimal clinical communication. Conclusion: This study identified multiple system-level factors contributing to opioid errors in inpatient palliative care services. Any quality and safety initiatives targeting safe opioid delivery in specialist palliative care services needs to consider the full range of contributing factors, from individual to systems/latent factors, which promote error-causing conditions.